Beyond the Silence - Peterson, Tracie; Woodhouse, Kimberly (Minneapolis, MN : Bethany House, 2016)
Lillian Porter is thrilled to accept a nanny position out west, until she arrives and hears troubling rumors that her employer caused his wife's death. But the accusation doesn't align with the man she comes to know--and love. When Woody is arrested on suspicion of attacking his housekeeper, can Lillian find the truth in time to save them both from tragedy?
Keywords: Nannies -- Fiction; Single fathers -- Fiction; Widowers -- Fiction; Man-woman relationships -- Fiction; California -- Fiction -- History -- 19th century; Christian fiction; Romance fiction; Historical fiction